2021
DOI: 10.1021/acsaem.1c00265
|View full text |Cite
|
Sign up to set email alerts
|

Firing-Stable PECVD SiOxNy/n-Poly-Si Surface Passivation for Silicon Solar Cells

Abstract: Passivating contacts based on SiO x /poly-Si exhibit excellent contact and surface passivation properties enabling very high solar cell conversion efficiencies. In this paper, we investigate and optimize the plasmaenhanced chemical vapor deposition (PECVD) of SiO x N y /n-a-Si stacks, their subsequent annealing to SiO x N y /n-poly-Si stacks followed by PECVD SiN x deposition and firing. We eliminate blistering of the poly-Si layer by enabling a controlled hydrogen out-diffusion during the annealing step. Wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 44 publications
(62 reference statements)
1
17
0
Order By: Relevance
“…A further supporting argument for the hypothesis of an important role of mechanical stress for the degradation of POLO junction upon firing is the recent observation of Stöhr et al 49 that junctions with a PECVD-SiO z N y -based interfacial oxide-whose thermal expansion coefficient (2.2-2.6 Â 10 À6 /K), 50 depending on the deposition parameters, can be much closer to that of (poly-)Si than that of thermally grown SiO z -show a significantly improved firing stability.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…A further supporting argument for the hypothesis of an important role of mechanical stress for the degradation of POLO junction upon firing is the recent observation of Stöhr et al 49 that junctions with a PECVD-SiO z N y -based interfacial oxide-whose thermal expansion coefficient (2.2-2.6 Â 10 À6 /K), 50 depending on the deposition parameters, can be much closer to that of (poly-)Si than that of thermally grown SiO z -show a significantly improved firing stability.…”
Section: Discussionmentioning
confidence: 76%
“…These results allow further optimization of the passivation quality of POLO junction after firing, which includes the choice of dielectric capping layers and an adjustment of the firing belt speed. In addition, the choice of an intermediate layer with a higher thermal expansion coefficient, which is, therefore, more suitable with c‐Si and poly‐Si, such as SiN y O x , 49 can be selected to increase the firing stability. However, this layer must also provide a good contact resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The firing stability of n‐type poly‐Si passivating contacts has been studied by a number of research groups 11–18 . In our recent work, 19 a pronounced surface degradation was observed on n‐type ex‐situ phosphorus‐doped poly‐Si contacts fired either with or without the presence of SiN x capping layers at above 800°C, with the degradation extent depending on various processing parameters, such as the growth of interfacial SiO x , the poly‐Si deposition temperature, the phosphorus diffusion conditions, and the dielectric capping layer.…”
Section: Introductionmentioning
confidence: 97%
“…[9][10][11] The firing stability of n-type poly-Si passivating contacts has been studied by a number of research groups. [11][12][13][14][15][16][17][18] In our recent work, 19 a pronounced surface degradation was observed on n-type ex-situ phosphorus-doped poly-Si contacts fired either with or without the presence of SiN x capping layers at above 800 C, with the degradation extent depending on various processing parameters, such as the growth of interfacial SiO x , the poly-Si deposition temperature, the phosphorus diffusion conditions, and the dielectric capping layer. In other work, 20 we proposed a hypothesis that an excessive amount of hydrogen released from the dielectric capping layer to the poly-Si/ SiO x structure, particularly surrounding the interfacial SiO x , causes the degradation after firing.…”
mentioning
confidence: 99%
“…The annealing process plays a crucial role in obtaining a high carrier lifetime in the hydrogenation from the film to the c-Si surface. Some studies related to post-annealing have been reported [26][27][28][29][30]. Microwave annealing (MWA) is a new and effective method to obtain high-carrier-lifetime thin films.…”
Section: Introductionmentioning
confidence: 99%